Digital interaction: the key to forming and developing digital skills in high school mathematics - Druța, Rodica (CEP USM, 2024)
This article explores the essential role of digital interaction in shaping and developing digital skills in high school mathematics education. By integrating technology into the educational process, students are exposed to a variety of digital tools and resources that help them understand complex mathematical concepts and develop practical skills. From using interactive applications and online learning platforms to simulations and educational games, digital interaction provides students with significant opportunities to experience, practice, and apply mathematical knowledge in a stimulating virtual environment. Through these digital experiences, students acquire not only essential mathematical skills but also valuable digital skills that are indispensable in the modern world.

Acest articol explorează rolul esențial al interacțiunii digitale în formarea și dezvoltarea competențelor digitale la disciplina matematică în cadrul învățământului liceal. Prin integrarea tehnologiei în procesul educațional, elevii sunt expuși la o varietate de instrumente și resurse digitale care îi ajută să înțeleagă concepte matematice complexe și să-și dezvolte abilitățile practice. De la utilizarea aplicațiilor interactive și a platformelor de învățare online până la simulările și jocurile educative, interacțiunea digitală oferă elevilor oportunități semnificative de a experimenta, de a practica și de a aplica cunoștințele matematice într-un mediu virtual stimulativ. Prin intermediul acestor experiențe digitale, elevii dobândesc nu doar competențe matematice esențiale, ci și abilități digitale valoroase care sunt indispensabile în lumea modernă.
Interacțiunea digitală: cheia formării competențelor digitale la matematică în liceu
Keywords: digital interaction; digital skills; mathematics; high school education; interacțiune digitală; competențe digitale; matematică; liceu; formare